Establishing International Blood Pressure References Among Nonoverweight Children and Adolescents Aged 6 to 17 Years. Issue 4 (26th January 2016) - Xi, Bo; Zong, Xin'nan; Kelishadi, Roya; Hong, Young Mi; Khadilkar, Anuradha; Steffen, Lyn M.; Nawarycz, Tadeusz; Krzywińska-Wiewiorowska, Małgorzata; Aounallah-Skhiri, Hajer; Bovet, Pascal; Chiolero, Arnaud; Pan, Haiyan; et al.
Abstract : Background—: Several distributions of country-specific blood pressure (BP) percentiles by sex, age, and height for children and adolescents have been established worldwide. However, there are no globally unified BP references for defining elevated BP in children and adolescents, which limits international comparisons of the prevalence of pediatric elevated BP. We aimed to establish international BP references for children and adolescents by using 7 nationally representative data sets (China, India, Iran, Korea, Poland, Tunisia, and the United States). Methods and Results—: Data on BP for 52 636 nonoverweight children and adolescents aged 6 to 19 years were obtained from 7 large nationally representative cross-sectional surveys in China, India, Iran, Korea, Poland, Tunisia, and the United States. BP values were obtained with certified mercury sphygmomanometers in all 7 countries by using standard procedures for BP measurement. Smoothed BP percentiles (50th, 90th, 95th, and 99th) by age and height were estimated by using the Generalized Additive Model for Location Scale and Shape model. BP values were similar between males and females until the age of 13 years and were higher in males than females thereafter. In comparison with the BP levels of the 90th and 95th percentiles of the US Fourth Report at median height, systolic BP of the corresponding percentiles of these international references was lower, whereas diastolic BP was similar. Conclusions—: These international BP references will be a useful tool for international comparison of the prevalence of elevated BP in children and adolescents and may help to identify hypertensive youths in diverse populations. Abstract : Supplemental Digital Content is available in the text.